Modelagem matemática e numérica para inicialização do escoamento em golfadas de gás-líquido - Conte, Marco Germano (2013)
Many industrial processes like oil transportation in pipelines operate on two-phase flow regime, especially in slug flow pattern. The slug flow is characterized by the intermittent succession of liquid slugs, which have a large momentum, followed by long bubbles of compressible gas. The slug flow has been a topic of research in the last decades; however, there are few mathematical models for this complex flow. One can list the Eulerian two-fluid and drift flux, and the Lagrangian slug-tracking. The slug-tracking model is less computationally expensive and allows the simulation of long pipes, since it is not mesh dependent. However, it requires well-defined initial conditions at the pipe inlet. In this context, a Lagrangean methodology to capture the process of slug initiation is presented in this work for horizontal and near horizontal pipes. Starting from one dimensional two-fluid model, the equations of momentum and mass conservation were simplified. The motion generated by the dynamic pressure of the gas was decoupled of the slow movement of the liquid film. The system of equations resulting for the gas domain was discretized using the method of finite differences and solved with the TDMA algorithm. The liquid motion in the bubbles was then modeled by a modified version of shallow water equations. A software was developed using Intel Visual Fortran language to simulate the process of slug initiation on a gas-liquid stratified flow. The waves growth in the liquid-gas interface was monitored numerically until one of them reach the top of pipe and form a slug. Numerical simulations were performed for different flow conditions of liquid-gas, in order to evaluate the model ability to generate slugs. The results showed consistency and have potential to be used as a tool for initialization and simulation of slug flow.